Comparison of Polyunsaturated Fatty Acids in Depressed Patients Attempted Suicide with Healthy Controls - MR Khanmohammadi,; F Abdi; R Haji Hoseini,; M Rafieian (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2010)
BACKGROUND AND OBJECTIVE: The role of polyunsaturated fatty acids (PUFA) especially omega-3 has been explored in many diseases. However, the profile of PUFA in depressed patients is not established. The aim of this study was to measure the amount of DHA (Docosahexaenoic acid) and EPA (Eicosapentaenoic acid) in depressed and suicide group, compared to control group. METHODS: In a case–control study the amount of DHA and EPA in blood of 27 depressed patients, 32 attempted to suicide patients and 35 normal people were measured by gas-chromatography and then compared.FINDINGS: The amount of DHA in depressed and attempted to suicide patients and control group was 2.48±0.22, 2.25±0.24 and, 4.6±0.13 mg/ml, respectively (p<0.001). However, there was not significant difference between depressed and attempted to suicide patients in this regard. The amount of EPA in attempted to suicide patients (0.44±0.05 mg/ml) was less in comparison to depressed (0.84±0.20 mg/ml) or control (0.95±0.11 mg/ml) groups (p<0.001).CONCLUSION: It seems that there is a relation between the amount of DHA or EPA and attempt to suicide in depressed patients. However, in less severe depressed patients just DHA is changed, not EPA.